Isolation and characterization of cDNA clones encoding a novel subfamily sporamin B in sweet potato - Jollanda Effendy; Don R. LaBonte; Darda Efendi (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Effendy J, Labonte DR, Efendi D. 2019. Isolation and characterization of cDNA clones encoding a novel subfamily sporamin B in sweet potato. Biodiversitas 20: 3033-3041. Three cDNAs (IbH23, IbH41, and IbH74) encoding sporamin of sweet potato, were isolated from a skinning injury cDNA library. The open reading frame consisted of 288 nucleotides and the deduced polypeptide sequences consist of 96 amino acids with missing 127 amino acid residues at 5?. The sequences shared identity [42-62% (IbH23 and IbH41) and 40-61% (IbH74)] to sporamins A and B previously identified in other sweet potato species. The IbSpors contained three of four signature cysteine residues of sporamin family (Cys135, Cys198, Cys209). In addition to similarity to sporamins, these cDNA clones also showed similarities to miraculin (29-35%); Kunitz trypsin inhibitor (29-36%); factor Xa inhibitor (32-38%); subtilisin inhibitor (26-37%); seed protein (32%); tumor-related protein (36% in IbH23 and IbH41); and [wound-responsive protein (30%), sexual organ responsive protein (29%), and proteinase inhibitor (26%) can only be found in IbH74]. The three partial mRNA transcripts showed induced and transient expression in response to skinning injury. The phylogenetic analysis revealed that they belonged to a new member of sporamin gene subfamily B and may play key roles in plant defense and wound repair in response to skinning injury in storage roots of sweet potato.